Prosthetics rehabilitation in elderly with functional dyspepsia - Marcia Hortensia Corona Carpio; Charles Anthony López Verdecia; Ana Duharte Escalante; Miroslava Catellanos González; Zulema Chávez González (Centro Provincial de Información de Ciencias Médicas, 2018)
A descriptive and cross-sectional study of 71 elderly with functional dyspepsia, assisted in the Gastroenterology Service of "Asdrúbal López Vázquez" Southern Polyclinic in Guantánamo, was carried out from May, 2012 to the same month in 2014, with the objective of evaluating the effectiveness of the prosthetics rehabilitation in these patients.  In the series there was a prevalence of the female sex (53.7 %), 60-69 age group (53.7 %) and early sensation of filling as main symptoms, as well as the lost teeth, according to the dental mortality rate (30.4 %). The rehabilitative treatment allowed to eliminate almost all the symptoms found, reason why it was effective and constitutes an element to take into account to eliminate or diminish the symptoms in elderly with this disorder.